Keragaan Hasil Beberapa Galur Harapan Kacang Tanah di Lahan Sulfat Masam dan Lahan Lebak Dangkal - , Koesrini; Aidi Noor; , Sumanto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2006)
High soil acidity is one of the problems caused low groundnut productivity on South Kalimantan. Using adaptive variety is one effort for increasing yield. The objective of this research was to determine the yield performance and tolerance of groundnut to soil acidity on swamp areas. This research was conducted on acid sulphate soil at Jajangkit Timur-Batola-South Kalimantan on wet season of 2003/04 and on swamp area at Setiap-Pandawan-Hulu Sungai Tengah-South Kalimantan on dry season of 2003. This research was arranged in Randomized Complete Block Design with three replications. Twelve genotypes and 3 check varieties i.e. Jerapah, Singa and Lokal variety, were tested on those regions.The result showed that some groundnut promising lines had good performance on acid sulphate soil and swamp areas. Performance of yield and its component  were influenced by soil environment, i.e. soil acidity, Ca content and Al saturated. The best five promising lines on acid sulphate soil were GH-3, GH-4, GH-5, GH-8 and GH-9, while on swamp area were GH-2, GH-5, GH-6, GH-9 and GH-11. Two promising lines, i.e. GH-5 and GH-9, performed better on both areas.   Key words: Performance, groundnut, swamp areas